Unveiling Risk Patterns of Disability Progression A Clustering Based Transition Matrix Analysis Using Indonesian National Data - Setiawan, Ariyono; Bin Abdul Hadi, Abdul Razak; Faller, Erwin; Wibawa, Aji Prasetya (Research Group of Data Engineering, Faculty of Informatics, 2025)
This study investigates the progression of disability severity from